Asi Eksklusif Dan Tingkat Kecerdasan Anak Di Taman Kanak-Kanak Exclusive Breastfeeding And The Intelligence Of Children In Kindergarten - Murdiningsih Murdiningsih; Chairuna MB; Aprillia Ayu SY (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2014)
Breast milk is a complex biological fluid containing all the nutrients the kids body needs. Adequate nutrition is very influential on the growth and development especially in the first years of life in which the child is experiencing unprecedented growth , especially the growth of the brain. The objective of this research was to determine the relationship of exclusive breastfeeding on the level of intelligence of children in kindergarten Wilayah Kemuning District of Palembang in 2013 .Design of the research is analytical research with cross sectional approach to collecting primary data (perspective). Of the 10 kindergarten located in Palembang Kemuning district area , researchers took a random TK 5 to obtain a sample of 64 respondents . The result is most of the mothers given exclusive breastfeeding in children of 64.1 % , the child had a avarage intelligence level ( on average ) that is equal to 81.3 %. Statistical found no significant association between exclusive breastfeeding and level of intelligence of children with p value 0.099 and OR 3,150 ( 0867-11442 ). Conclusion, exclusive breastfeeding is not a major factor in determined the level of intelligence in children, that exclusive breastfeeding did not have a significant relationship to the child's level of intelligence.